Evidences of scientific literacy in spellings of illustrations on the CTSA perspective at Chemistry Teaching - Moretti, Andressa Algayer da Silva (2021)
This article aims to present evidences of Scientific Literacy (SL) of graphic and discursive illustrations structured by students of the 2º year of high school, after the application of a didactic sequence (DS) named “What is the chamistry that you breath?” made on the Science, Technology, Society and environment (STS) perspective. The DS was arranged based on the three pedagogical moments (3PM) and applied in four presencial meets of two class hours per meet. It was proposed as na evaluative activity for the students to create a story that comtemplated the thermochemistry subject they had in class. For the qualitative analyzis it was used the analyzis of content of Bardin (2011) and the pre-estabilished categories related to the indicators of SA proposed by Sasseron and Carvalho (2008: 2010). The approach created an environment of reflection making use of the observations of dynamical relations between the STSE elements on the school context, with the citizen training of the students, because the development of critical tought favored the elaboration of proposals for solving social and environmental problems, evidenced on the stories created. It was noticed that the students were capable to connect the chemistry concepts showed on the DS to the effects of the atmospheric polution on the environment and on health.